2019
DOI: 10.1016/j.ebiom.2019.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the gut microbiota transcends genetic determinants of malaria infection severity and influences pregnancy outcome

Abstract: Background: Malaria infection in pregnancy is a major cause of maternal and foetal morbidity and mortality worldwide. Mouse models for gestational malaria allow for the exploration of the mechanisms linking maternal malaria infection and poor pregnancy outcomes in a tractable model system. The composition of the gut microbiota has been shown to influence susceptibility to malaria infection in inbred virgin mice. In this study, we explore the ability of the gut microbiota to modulate malaria infection severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 110 publications
1
27
0
Order By: Relevance
“…A related study that we conducted recently supports this idea, and suggests that this impact likely outweighs maternal post-partum behavior. Neonates born to Swiss Webster dams that exhibited patterns of infection like those reported here displayed the same tendency to perish during the first four days of life, even when fostered on uninfected Swiss Webster dams 56 . In humans, low birth weight is associated with a significantly higher risk of infant death, regardless of etiology.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…A related study that we conducted recently supports this idea, and suggests that this impact likely outweighs maternal post-partum behavior. Neonates born to Swiss Webster dams that exhibited patterns of infection like those reported here displayed the same tendency to perish during the first four days of life, even when fostered on uninfected Swiss Webster dams 56 . In humans, low birth weight is associated with a significantly higher risk of infant death, regardless of etiology.…”
Section: Discussionsupporting
confidence: 68%
“…In this work, severe infection was associated with significant hemozoin accumulation, elevated transcripts for Ifng , Il10 , and Mgl2 , a marker for monocyte/macrophages in conceptuses, and reduced maternal vascular space in the placenta. These findings were coincident with reduced fetal weight at term and reduced survival in the first four days of life 56 . In addition to placental pathology, a stasis in pregnancy-associated weight gain was observed in infected mice between GD/ED 9 and GD/ED 11.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Despite this, Swiss Webster mice do exhibit a genetic susceptibility to diabetes, as spontaneous development of obesity-associated polyuric, polydipsic, glucosuric, and hyperglycemic symptoms were observed previously [39]. Subsequently, Swiss Webster mice are reasonably prone to DIO, and the research community uses commercially available GF Swiss Webster mice for IMB transplant studies [36,[39][40][41][42][43][44][45][46][47]. Bäckhed and colleagues recently developed a simplified human IMB model using GF Swiss Webster mice that holds promise in the study of diet-host-microbiota interactions in relation to obesity and MetS [40].…”
Section: Author/yearmentioning
confidence: 99%
“…Recently, some scholars suggested that gut microbiome remodeling during pregnancy is a positive reaction of the mother and necessary for a successful pregnancy, which may contribute to the state of the immunity and metabolism (Konstantinov et al, 2013). However, more researchers believe that changes in gut microbiome during pregnancy are harmful to pregnant women and will cause related complications (Morffy Smith et al, 2019).…”
Section: Alterations Of Gut Microbiome During Pregnancymentioning
confidence: 99%